2016
DOI: 10.7861/futurehosp.3-3-178
|View full text |Cite
|
Sign up to set email alerts
|

The Future Hospital: a blueprint for effective delirium care

Abstract: Newcastle University ePrints -eprint.ncl.ac.uk Richardson SJ, Fisher JM, Teodorczuk A. The Future Hospital: a blueprint for effective delirium care.Delirium remains the most common hospital complication. Occurrence rates are set to rise as the population ages and, despite being preventable and treatable, delirium continues to be under-recognised. Given the adverse outcomes associated with delirium and the considerable fi nancial burden, patients with delirium must be considered 'core business' for 21st century… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Multiple reasons exist for under-diagnosis, including, amongst others, a general lack of delirium training at all levels including in undergraduate education 249 , attitudes such as the perception that delirium is not 'owned' by (that is, the responsibility of) certain specialties or groups of practitioners 250 , the use of imprecise alternative terms such as 'confusion' , and a lack of perception that delirium is important. It is now clear that successful implementation of delirium detection, treatment and risk reduction is a complex challenge 251 , requiring an educational programme addressing both attitudes and skills, supported by audit, and using tools with proven implementability and tailored to the population to be tested. A study using quality improvement methodology to develop a digital pathway demonstrated the promise of this combined approach to improve delirium assessment and detection 252 .…”
Section: Challenges In Detecting Deliriummentioning
confidence: 99%
“…Multiple reasons exist for under-diagnosis, including, amongst others, a general lack of delirium training at all levels including in undergraduate education 249 , attitudes such as the perception that delirium is not 'owned' by (that is, the responsibility of) certain specialties or groups of practitioners 250 , the use of imprecise alternative terms such as 'confusion' , and a lack of perception that delirium is important. It is now clear that successful implementation of delirium detection, treatment and risk reduction is a complex challenge 251 , requiring an educational programme addressing both attitudes and skills, supported by audit, and using tools with proven implementability and tailored to the population to be tested. A study using quality improvement methodology to develop a digital pathway demonstrated the promise of this combined approach to improve delirium assessment and detection 252 .…”
Section: Challenges In Detecting Deliriummentioning
confidence: 99%